Innovationsförderung durch die EU-Strukturpolitik nach 2007: neue Ansätze, alte Probleme? - Wink, Rüdiger (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
This paper deals with options, prerequisites and planned activities to foster innovation promotion as a major instrument of EU structural funds. Due to its dependence on a specific density of agglomeration and interactions between firms, research institutes, universities, public administration and specialised intermediaries, regional innovation systems (RIS) and clusters seem to be a very promising instrument to improve the competitiveness of regions and their citizens, firms and other organizations. However, only few regions are able to implement a strategy of RIS or clusters successfully, causing additional risks of increasing disparities between economically leading and lagging regions. The plans of the European Commission for the next budget period including further instruments to promote innovation are investigated and assessed critically, and within conclusions, an argumentation is presented, why promotion of innovation will never contribute in the intensity intended by the European Commission to EU regional policy.